Cross-talk between traditional Chinese medicine and Parkinson's disease based on cell autophagy - Mufei Wang; Hongsong Yu; Yihuai He; Shusheng Liao; Delin Xu (Elsevier, 2023)
Background: Parkinson's disease (PD) is the second most common neurodegenerative movement disorder, with an unclear specific pathogenesis. There is no existing method that can reverse the development of PD. Importantly, researchers need to explore a new treatment rapidly for PD. Methods: The literature search was performed in the past 10 years in PubMed and China National Knowledge Infrastructure (CNKI) on the treatment of PD via autophagy regulation, expands the dialectical thinking of traditional Chinese medicines (TCMs) for PD, and systematically assesses the pharmacological mechanism of TCMs and their compound preparations in the therapy of this disease. Results: Previous studies have reported that TCMs exert neuroprotective effects by regulating autophagy. TCMs can be multitargeted to impact autophagy, alleviating symptoms in patients with PD. Conclusion: This study can provide novel ideas and a theoretical basis for the treatment of PD.